2021
DOI: 10.3892/etm.2021.11017
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activation in gestational diabetes mellitus placentas is associated with hydrogen sulfide synthetase deficiency

Abstract: The placenta may play a key role in the activation of inflammation and initiation of insulin resistance (IR) during gestational diabetes mellitus (GDM) pathogenesis. Interleukin (IL)-1β and IL-18, regulated by NLR family pyrin domain containing-3 (NLRP3) inflammasome, are important inflammatory cytokines in the initiation of maternal IR during GDM. However, the mechanism responsible for the regulatory of NLRP3 inflammasome in placenta remains unknown. Hydrogen sulfide (H 2 S) exerts anti-inflammatory function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Thus, we propose the possibility that miR-17-5p could NLRP3 inflammasome participates in the regulation of interleukin (IL)-1β and IL-18, 30 which have been considered as important inflammatory cytokines in the development of insulin resistance during GDM. 31 Wu et al found the excessive activation of NLRP3 inflammasome in GDM placental tissues, 32 which was consistent with our results. Besides, NLRP3 inflammasome activation can impair insulin sensitivity by promoting macrophage-T cell activation in adipose tissues.…”
Section: Dovepresssupporting
confidence: 93%
“…Thus, we propose the possibility that miR-17-5p could NLRP3 inflammasome participates in the regulation of interleukin (IL)-1β and IL-18, 30 which have been considered as important inflammatory cytokines in the development of insulin resistance during GDM. 31 Wu et al found the excessive activation of NLRP3 inflammasome in GDM placental tissues, 32 which was consistent with our results. Besides, NLRP3 inflammasome activation can impair insulin sensitivity by promoting macrophage-T cell activation in adipose tissues.…”
Section: Dovepresssupporting
confidence: 93%
“…Future works should explore the expression levels of IL-12 in patients with CVD and evaluate the pathophysiological consequences of IL-18 overexpression. In particular, due to the association of this cytokine with the NLRP3 inflammasome-a system commonly increased in pathological pregnancies [50,51]-further efforts might be directed to explore this component in women with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta is crucial in the pathogenesis of gestational diabetes mellitus (GDM) [169]. In GDM, deficiency of H 2 S-producing enzymes in the placenta results in excessive activation of the NLRP3 inflammasome, an important inflammatory cytokine involved in the initiation of maternal insulin resistance [111]. Therefore, H 2 S may be involved in the pathogenesis of GDM by controlling NLPR3 inflammasome activation in the placenta.…”
Section: H 2 S Improves Placental Oxidative Damagementioning
confidence: 99%